Web Services and Formal Methods 5th International Workshop, WS-FM 2008, Milan, Italy, September 4-5, 2008, Proceedings - Bruni, Roberto; Wolf, Karsten (Programming and Software Engineering, 2009)
This book constitutes the thoroughly refereed post-workshop proceedings of the 5th International Workshop on Web Services and Formal Methods, WS-FM 2008, held in Milan, Italy, in September 2008 in conjunction with the 6th International Conference on Business Process Management, BPM 2008. The 13 revised full papers presented together with one invited paper were carefully reviewed and selected from 39 submissions. The papers feature topics such as analysis, test, and verification; choreographies and process calculi; transactions and interoperability; workflows and petri nets.